INVESTIGATING ATMOSPHERIC AIR QUALITY IN UKRAINE THROUGH CIVIC MONITORING: A CASE STUDY OF THE CITY OF ZAPORIZHZHIA - Skuibida, Olena (Collection of scientific papers «ΛΌГOΣ», 2024)
Introduction. Military operations have had a significant impact on air pollution in Ukraine. New sources of pollutant emissions have emerged, and the spatial distribution of emission sources has shifted due to the destruction of infrastructure, industrial facilities, and the use of ammunition. As a result, air pollution has worsened, particularly with toxic chemicals and greenhouse gases, while climate change processes have been exacerbated. Therefore, the need for continuous air pollution monitoring is especially critical during wartime.